Big data analytics in the insurance market - Sood, Kiran; Balusamy, Balamurugan; Grima, Simon; Marano, Pierpaolo (Emerald Publishing, 2022)
Big Data Analytics in the Insurance Marketis an industry-specific guide to creating operational effectiveness, managing risk, improving financials, and retaining customers. A must for people seeking to broaden their knowledge of big data concepts and their real-world applications, particularly in the field of insurance.--Resumé vydavatel
Keywords: big data; pojišťovnictví; zpracování dat; pojišťovny; insurance; data processing; insurance companies; elektronické knihy; kolektivní monografie; electronic books; collective monographs